A Choreopolitics to Be Knead - Calisto Echeveste, Emilia (2023)
Herein are presented some of the results of a larger ethnographic research carried out in the field of contemporary dance, which is circumscribed to what has been named as the southernmost circuit in Montevideo, Uruguay. Inquiries and conclusions are reviewed, particularly the ones about the aesthetic-political potential this dance has when it is pushed to its boundaries and when some inherited choreographic structures are dislocated. Besides, a brief reflection is developed on the possibility of opening ruptured lines, from dance practices to a widened field. The methodology used was ethnographic, it was approached from a phenomenological anthropological perspective and from embodiment. Specifically, the analysis focuses on two choreographic proposals, in which the researcher enactively participated, articulating the register with the concepts micropolitics (Deleuze & Guattari, 2004) and choreopolitics (Lepecki, 2016), among others. Conclusions remark that in the cases wherein contemporary dance presents non-policed choreographies, certain practitioners materialize a potential of change, which for others operate just as part of the doxa of the wider dance field.